1993
DOI: 10.1006/cbir.1993.1075
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis or programmed cell death?

Abstract: Although there are different ways in which cells may die, it is now thought that in a developmental context cells are induced to positively commit suicide whilst in a homeostatic context the absence of certain survival factors may provide the impetus for suicide. There appears to be some variation in the morphology and indeed the biochemistry of these suicide pathways; some treading the path of "apoptosis", others following a more generalized pathway to deletion, but both usually being genetically and syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(42 citation statements)
references
References 6 publications
4
36
0
2
Order By: Relevance
“…The nuclear and nucleolar alterations observed in the treatment groups (206 ppm, 1031 ppm and 2062 ppm of permethrin) corroborate Kerr et al [31], who reported nuclear alterations in apoptotic cells, including fragmentation and enlargement of the nucleus, chromatin marginalization and fragmentation of the nucleolus, resulting from the biochemical and morphological alterations in the nucleus during apoptosis [29,[32][33][34][35][36]. Thus, considering the similarities between the nuclear [18] and nucleolar alterations found in this study, it can be inferred that the salivary glands of semi-engorged R. sanguineus s. l. females subjected to different concentrations of permethrin would also be undergoing the process described by Kerr et al [31]; i.e., apoptotic death.…”
Section: Discussionsupporting
confidence: 77%
“…The nuclear and nucleolar alterations observed in the treatment groups (206 ppm, 1031 ppm and 2062 ppm of permethrin) corroborate Kerr et al [31], who reported nuclear alterations in apoptotic cells, including fragmentation and enlargement of the nucleus, chromatin marginalization and fragmentation of the nucleolus, resulting from the biochemical and morphological alterations in the nucleus during apoptosis [29,[32][33][34][35][36]. Thus, considering the similarities between the nuclear [18] and nucleolar alterations found in this study, it can be inferred that the salivary glands of semi-engorged R. sanguineus s. l. females subjected to different concentrations of permethrin would also be undergoing the process described by Kerr et al [31]; i.e., apoptotic death.…”
Section: Discussionsupporting
confidence: 77%
“…In a landmark paper, Schweichel and Merker (1973) described three different types of active cell death in embryonic tissues: apoptosis, autophagic cell death and, finally, nonlysosomal disintegration. Recent reports also distinguish several morphological types of programmed or active cell death and emphasize that the terms 'programmed cell death' and 'apoptosis' are not interchangeable (Lockshin and Zakeri, 1991; Bowen, 1993;Schwartz et al, 1993;Bursch and Grasl-Kraupp, 1994;Majno and Joris, 1995). Recently a monoclonal antibody BV 2 was isolated which recognizes an antigen expressed during avian programmed cell death in both apoptotic and certain necrotic cells, indicating that these cell-death patterns may share similar biochemical features (Fernandez et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis has also been proven as a major cause of cytopathogenicity in some virus systems (Jeurissen et al, 1992 ;Laurent-Crawford et al, 1993 ;Levine et al, 1993 ;Hinshaw et al, 1994 ;Esolen et al, 1995). In addition, enhancement of cytosolic calcium can trigger the apoptotic response (Bowen, 1993). We are currently testing whether poliovirus infection induces apoptosis in Vero cells.…”
Section: Discussionmentioning
confidence: 99%